Students’ Perspectives on the Usefulness of ICT-Based Learning by Using Technology Acceptance Model (TAM) - Amrullah, Amrullah; Lail, Husnul; Sumayani, Sofia Rahmi; Hamzah, Nurul Huda Binti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. In this new era, teaching and learning activities have been associated with the use of Information and Communication Technology (ICT). In the context of English language learning, ICT is a resource and tool for supporting students in their learning process. With the use of different English learning activities, ICT offers students a range of sources to obtain authentic content and improve their language abilities. This research aims to analyze the English as a Foreign Language (EFL) students’ perspectives on the use of ICT-based learning in their learning activities and the contribution of ICT-based learning to the learning activities. This is a quantitative descriptive study. The Technology Acceptance Model (TAM), developed by Davis (1985) and improved version used in ELT classroom activities by Castro (2019) were incorporated in this study.  31 students from the English language Department of University Mataram were the sample of the study. The data were gathered using three instruments which are online questionnaire, interview, and documentation. The instruments used in this study to examine the perspectives of EFL students on ICT-based learning. The findings are analyzed using SPSS, and Spearman's Rho test. This is to determine how closely the two variables (ICT and Learning English} are related. The findings showed that the majority of the students have positive perspectives on ICT-based learning because it is relatively easy to use, and learning activities is significantly correlated with its usefulness. Given that the two variables in the data have a linear relationship and a positive correlation coefficient (0.665).  Thus, it can be concluded that the better ICT quality improves, the better the quality of students' English learning.Keywords: English as a Foreign Language (EFL), Students Perspectives, Information and Communication Technology (ICT), Technology Acceptance Model (TAM)